ANALISIS KELAYAKAN USAHA BUDIDAYA PEMIJAHAN IKAN LELE MUTIARA (Clarias gariepinus) CV. HARAPAN LUNAS JAYA DESA LAE BUTAR KECAMATAN GUNUNG MERIAH KABUPATEN ACEH SINGKIL - Asbaruddin Zebua; Nur Rahmat (Agros Journal of Agriculture Science, 2023)
Indonesia is potential in developing freshwater fish farming dominated by pearl catfish (Clarias gariepinus).  The popularity of pearl catfish is due to its very soft flesh and few thorns, also supported with its fast growth and considered easy treatment.  This leads to the high interest of fishery business actors in developing their business, especially in aquaculture sub-sector. The objectives of this study are to determine the amount of revenue received by entrepreneurs and the feasibility of the pearl catfish (Clarias gariepinus) nursery business of CV.  Harapan Lunas Jaya, Lae Butar Village, Gunung Meriah District, Aceh Singkil Regency.Data collection method used in this research is direct interviews to employers (sample) using a list of questions (questionnaire).  Data analysis used is analysis of income, revenue, feasibility (R/C, B/C, NPV, IRR.) and BEP. Research results showed that the production cost of the pearl catfish (Clarias gariepinus) nursery business released in the first year was IDR. 60,861,500 and the second year of IDR. 37,066,000 and a total investment of IDR. 97,927,500. Meanwhile, the amount of production of the first year was 600,000 pearl catfishes and in the second year 600,000 pearl catfishes valued at IDR.300/each. So that the amount of revenue in the first year was IDR 180,000,000 and the amount of revenue in the second year was IDR. 180,000,000.   Meanwhile, the amount of revenue earned in the first year was IDR. 119,138,500, and second year income of  IDR.142,934,000. The R / C Ratio value obtained is 2.9, which means that this business is feasible to be developed.  The value of B / C Ratio is 1.9, which means that the business is profitable. The amount of BEP for receipts is IDR. 29,744,375, production,  BEP of 202,872 / pearl catfish and BEP price of 101 / pearl catfish. while the NPV value is IDR.  116,563,028> 0, which means that it is feasible to be developed, and the IRR value is 96.0933%, which means that IRR > than the interest rate, so that the investment is profitable and feasible to proceed. Keywords: Feasibility of pearl catfish (Clarias gariepinus) nursery business INTISARIIndonesia memiliki potensi dalam pengembangan budidaya ikan air tawar yang dimana dinominasi oleh ikan lele mutiara (Clarias gariepinus). Populernya ikan lele mutiara dikarenakan daging nya Sangat lunak dan durinya juga sedikit, ditambah lagi dengan pertumbuhan nya yang cepat besar dan prawatanya terbilang mudah. Hal ini menunjukan tingginya minat para pelaku usaha perikanan dalam mengembangkan usahanya, terutama di sub sektor budidaya perikanan. Adapun tujun dari penelitian ini untuk mengetahui besarnya pendapatan yang diterima oleh pengusaha dan kelayakan dari usaha budidaya pemijahan ikan lele mutiara (Clarias gariepinus) ) CV. Harapan Lunas Jaya Desa Lae Butar Kecamatan Gunung Meriah Kabupaten Aceh Singkil. Metode pengumpulan data yang digunakan dalam penelitian ini adalah metode wawancara langsung terhadap pengusaha (sample) dengan menggunakan daftar pertanyaan (kuisioner). Analisis data yang digunakan adalah analisis pendapatan, penerimaan, keleyakan (R/C, B/C, NPV, IRR.) dan BEP. Hasil penelitian menunjukkan bahwa biaya produksi usaha budidaya pemijahan ikan lele mutiara (Clarias gariepinus) yang dikelurkan tahun pertama sebesar Rp 60.861.500 dan tahun kedua sebesar Rp 37.066.000 dan total investasi sebesar Rp 97.927.500. sedangkan jumlah produksi yang dihasilkan tahun pertama sebesar 600.000 ekor dan tahun kedua sebesar 600.000 ekor dengan harga perekor Rp. 300. Sehingga besarnya penerimaan tahun pertama sebesar Rp 180.000.000 dan penerimaan tahun kedua sebesar Rp 180.000.000. Sedangkan besarnya pendapatan yang diperoleh tahun pertama sebesar Rp 119.138.500, dan pendapatan tahun kedua sebesar Rp 142.934.000. Adapun nilai R/C Ratio yang diperoleh adalah 2,9 yang artinya usaha ini  layak untuk dikembangkan. Nilai B/C Ratio diperoleh sebesar 1,9 yang artinya usaha menguntungkan. Besarnya BEP penerimaan adalah sebesar Rp. 29.744.375, BEP produksi sebesar 202.872/ekor dan BEP harga sebesar 101/ekor. sedangkan nilai NPV sebesar Rp 116.563.028 > 0 yang artinya layak untuk dikembangkan, dan nilai IRR sebesar 96,0933% yang artinya IRR > dari tingkat suku bunga maka investasi menguntungkan dan layak untuk dilanjutkan. Keywords: Feasibility of pearl catfish (Clarias gariepinus) nursery business